Intention to adopt ChatGPT in higher education - Lee, Zi Wei (2024)
As Artificial Intelligence increasingly penetrates and transform education, these technological advancements will radically alter the existing approach to students' learning progress, thus transforming learning styles and teaching techniques. Hence, the objective of this study is to examine the relationship between perceived usefulness, perceived ease of use, hedonic motivation, and social influence towards the intention to adopt ChatGPT in higher education. In account of the ChatGPT context, researchers have made modifications to the Technology Acceptance Theory (TAM) and the Unified Theory of Technology Acceptance and Technology Use (UTAUT) and UTAUT 2 in order to identify a more suitable conceptual framework.